Mouse Strain-Dependent Difference Toward the Staphylococcus aureus Allergen Serine Protease-Like Protein D Reveals a Novel Regulator of IL-33 - Teufelberger, Andrea R.; Van Nevel, Sharon; Hulpiau, Paco; Nordengrün, Maria; Savvides, Savvas N.; De Graeve, Sarah; Akula, Srinivas; Holtappels, Gabriele; De Ruyck, Natalie; Declercq, Wim; Vandenabeele, Peter; Hellman, Lars; et al. (Frontiers in Immunology, 2020)
Staphylococcus aureus can secrete a broad range of virulence factors, among which staphylococcal serine protease-like proteins (Spls) have been identified as bacterial allergens. The S. aureus allergen serine protease-like protein D (SplD) induces allergic asthma in C57BL/6J mice through the IL-33/ST2 signalling axis. Analysis of C57BL/6J, C57BL/6N, CBA, DBA/2 and BALB/c mice treated with intratracheal applications of SplD allowed us to identify a frameshift mutation in the serine (or cysteine) peptidase inhibitor, clade A, member 3I (Serpina3i) causing a truncated form of SERPINA3I in BALB/c, CBA, DBA/2 mice. IL-33 is a key mediator of SplD induced immunity and can be processed by proteases leading to its activation or degradation. Full length SERPINA3I inhibits IL-33 degradation in vivo in the lungs of SplD-treated BALB/c mice, and in vitro by direct inhibition of mMCP-4. Collectively, our results establish SERPINA3I as a regulator of IL-33 in the lungs following exposure to the bacterial allergen SplD, and that the asthma phenotypes of mouse strains may be strongly influenced by the observed frameshift mutation in Serpina3i. The analysis of this protease-serpin interaction network might help to identify predictive biomarkers for type-2 biased airway disease in individuals colonized by S. aureus.